Starch wars: Rice, bread and South Asian difference in the French Enlightenment. (May 2015) - Smith, Blake
This article investigates the imperial dimensions of the French Enlightenment's science of diet, tracing their development in relation to perceptions of South Asian food. In the last years of the eighteenth century, political theorists, journalists, doctors and Orientalists became concerned with the effects of different staple grains, arguing over whether rice or wheat bread was most conducive to physical well-being and national power. Many of them invoked this dietary discourse on staples in order to scientifically justify European imperialism in South Asia. Journalist Simon-Henri-Nicolas Linguet, however, developed an alternative vision of the imagined connections between staple grains and politics. Linguet's work was a landmark in the conceptualisation of European 'gastro-politics', and suggests a road not taken by other Enlightenment critics of empire: a vision of dietary science, the body and the state that imagined European ventures abroad as a symptom of bad digestion.